The effect of schooling on earnings: The role of family background stuied by a large sample of Norwegian twins - Oddbjørn Raaum; Tom Erik Aabø (University of Oslo, Department of Economics, 1999)
A large representative sample of twins is used to estimate the causal effect of schooling on earnings in Norway, for both men and women. The within-twin-pair estimates reveal that standard cross section (OLS) estimates of the effect on male hourly earnings are biased upwards. For women, no such bias is found. However, family background seems to affect both educational attainment and post-schooling labour supply of women, implying that the standard estimate of the effect of schooling on female annual earnings is upward biased.
Keywords: 330; Bildungsertrag; Familiensoziologie; Norwegen